Infliximab in inflammatory bowel disease. (March 2019) - Papamichael, Konstantinos; Lin, Steve; Moore, Matthew; Papaioannou, Garyfallia; Sattler, Lindsey; Cheifetz, Adam S.
Anti-tumor necrosis factor (TNF) therapy has revolutionized the medical treatment of the inflammatory bowel diseases (IBD), Crohn's disease (CD), and ulcerative colitis. Twenty years ago, infliximab became the first anti-TNF agent approved for IBD. Data from randomized controlled trials, large observational cohort studies, postmarketing registries, and meta-analyses show that infliximab is a very effective treatment for moderate to severe IBD with a good safety profile. Infliximab has been also used to treat pouchitis following an ileal pouch–anal anastomosis (IPAA) after restorative proctocolectomy and to prevent postoperative recurrence following an ileocolonic resection for CD with good results. Nevertheless, up to 30% of patients show no clinical benefit following induction and up to 50% lose response over time. Both these unwanted outcomes can be largely explained by inadequate drug concentrations and frequently by the development of antibodies to infliximab. Loss of response can be managed efficiently and often prevented by applying therapeutic drug monitoring. Recently, the first biosimilars of infliximab have been approved and are utilized in clinical practice with comparable efficacy and safety with the originator. This review will mainly focus on the efficacy of infliximab in IBD.